Green Light‐Based Photobiomodulation with an Implantable and Biodegradable Fiber for Bone Regeneration (Small Methods 7/2020). Issue 7 (6th July 2020) - Jiang, Yuxi; Qi, Wei; Zhang, Qianyi; Liu, Hao; Zhang, Jianyun; Du, Ning; Nazempour, Roya; Su, Yuanzhe; Fu, Ruxing; Zhang, Kaiyuan; Lyu, Peijun; Dong, Fan; et al.
Abstract : Clear curative effects and limited penetration depth of short‐wavelength light (green and blue) have positioned challenges for in vivo applications of photobiomodulation. Green light has a definite osteogenic promotion effect in vitro. In article number 1900879, Xing Sheng, Yuguang Wang, and co‐workers establish a biodegradable optical fiber as a technology solution, and tests the expression of osteogenic related factors in vitro and in vivo.